Habitat suitability modeling for the endangered Hawaiian petrel on Kauai and analysis of predicted habitat overlap with the Newell’s shearwater - Jeff R. Troy (Global Ecology and Conservation, 2017)
The endangered Hawaiian petrel (Pterodroma sandwichensis) is endemic to the main Hawaiian Islands and has undergone a breeding range contraction since the arrival of humans. Using abiotic and biotic environmental variables, we developed a terrestrial habitat suitability model for the species on the island of Kauai based on contemporary sites where the species is known (or strongly suspected) to nest, as well as a habitat/threat-isolation index that combined predictions from this suitability model with spatial information on two anthropogenic threats to the species. After accounting for large-scale relative spatial positioning of sites in modeling procedures, the habitat suitability model suggests that the probability that a location on Kauai could be suitable for Hawaiian petrel nesting activity increases with increasing mean annual wind speed, and may also increase somewhat with increasing slope and native vegetation cover. The habitat suitability model (which does not incorporate spatial information on anthropogenic threats to the species) predicts approximately 74 km2 of Kauai, mostly in the interior of the island, as being potentially suitable with predicted probability > 0.7 for Hawaiian petrel terrestrial activity, and about 35 km2 with predicted probability > 0.9. Encouragingly, almost 50 km2 of land with predicted probability > 0.7 and almost 24 km2 with predicted probability > 0.9 is currently protected, being located on either government or private reserve land. Based on the habitat/threat-isolation index, most land predicted to be both suitable (based on environmental variables) and as isolated from threats as a large number of the known contemporary Hawaiian petrel sites, is found in government and private reserves. Some degree of predicted habitat overlap between the Hawaiian petrel and Newell’s shearwater (Puffinus newelli), another Hawaiian seabird of conservation concern, suggests that some of the same larger tracts of land could potentially be managed jointly for both species, as currently done in Upper Limahuli Preserve and Hono O Na Pali Natural Area Reserve on Kauai.